Regulatory risk under optimal incentive regulation - Roland Strausz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
The paper provides a tractable, analytical framework to study regulatory risk under optimal incentive regulation. Regulatory risk is captured by uncertainty about the policy variables in the regulator's objective function: weights attached to profits and costs of public funds. Results are as follows: 1) The regulator's reaction to regulatory risk depends on the curvature of the aggregate demand function. 2) It yields a positive information rent effect exactly when demand is convex. 3) Firms benefit from regulatory risk exactly when demand is convex. 4) Consumers' risk preferences tend to contradict the firms. 5) Benevolent regulators always prefer regulatory risk and these preferences may contradict both the firms and consumers' preferences.
Keywords: L51; D82; 330; Optimal incentive regulation; regulatory risk; procurement; information rents; Anreizregulierung; Regulierung; Wirtschaftspolitisches Ziel; Risiko; Informationswert; Rententheorie; Mikroökonomische Konsumfunktion; Theorie